Malaysia and RCEP Countries: Gain or Pain? - Marikan, Dayang Affizzah Awang; Arip, Mohammad Affendy; Khan, Jaber; Hamzah, Hazlin (Journal of Asian Scientific Research, 2020)
The study analyses the determinants of Malaysia’s export to RCEP (Regional Comprehensive Economic Partnership) using panel data of 15 countries for the period 1997-2018. The analysis shows that the Malaysia’s GDP and trade openness will increases as export increases. On the other hand, exchange rates have inverse relationship with export. Remoteness, however found to be insignificant to affect the export. Thus by joining RCEP, Malaysia can look forward to see the growth in its economies as well as attracting more foreign investors into the countries as the economies expanded and become more open. The economic benefit gain from the inverse relationship between export and exchange rate will further placed Malaysia to become more competitive in international markets. In the long run, the lower exchange rate will reduce imports and raise exports to compensate for the increase cost of exports.